1488 Paediatric Head Injuries: A London Trauma Centre Perspective. (October 2012) - Murray, F; Chandrashekhar, S
Abstract : Aims: Our aim was to determine the demographics, mechanism of injury and immediate outcome of a specific group of paediatric head injury patients: those who triggered 'trauma calls' and were initially managed in the emergency department (ED) resuscitation room due to either abnormal vital signs or a significant mechanism of injury. We also reviewed presentation times to assess the service provision implications. Methods: A retrospective review of all paediatric trauma patients managed initially in the resuscitation room over a three-year period. Data were collected from trauma notes and intensive care discharge summaries. Results: The total number of patients was 340. Of these 72% were male. The age breakdown was as follows: 31% less than 5 years, 33% aged 5 to 12 years and 35 % adolescent. The most common mechanisms of injury were road traffic accidents (RTA) with an incidence of 55%, and falls (31%). However in the pre-school group falls accounted for 53% of cases whereas in the 5–12 year group the incidence of RTAs was 70%. Assault caused 23% of presentations in the adolescent group. Regarding admissions, 63% were admitted for overnight observation, 27% required critical care and 0.1% died in the emergency department. Only 7% were discharged home from the ED. Peak presentation occurred from 15:00 to 21:00 hours. Conclusions: There are ongoing public health concerns regarding the mechanisms of injury. RTAs remain the leading cause of serious head injury but of note is the high number of pre-school children falling from significant heights at home.